2005
DOI: 10.1007/s11237-005-0030-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Composition of Mn-, Co- and Ni-Containing Perovskites on their Catalytic Properties in the Oxidative Coupling of Methane

Abstract: The catalytic properties of complex oxide catalysts with ABO 3 perovskite structure (A = Sr, Ba, La; B = Mn, Co, Ni) in the oxidative coupling of methane were studied with separate introduction of methane and oxygen onto the catalyst. The greatest catalytic activity was found for the nickel-containing oxides but these catalysts have much lower operational stability than Mn-and Co-containing catalysts. Modification of the oxide systems studied by partial replacement of the strontium or transition metal ions b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
2
5
0
Order By: Relevance
“…(d) The S BET values are smaller for perovskites and ferrites containing only two cations and these results appear to be caused by an effective increase in the degree of crystallinity as a result of the heat treatment. These values are comparable to those reported by other authors, 32 for similar chemical compositions.…”
Section: Materials Characterizationsupporting
confidence: 92%
“…(d) The S BET values are smaller for perovskites and ferrites containing only two cations and these results appear to be caused by an effective increase in the degree of crystallinity as a result of the heat treatment. These values are comparable to those reported by other authors, 32 for similar chemical compositions.…”
Section: Materials Characterizationsupporting
confidence: 92%
“…For Na-W-Mn/SiO2 catalyst, 12.0% CO selectivity, 12.9% CO2 selectivity and 69.0% C2 selectivity at 28.5% CH4 conversion are obtained, which are in agreement with several reports [21][22][23][24]. In a comparison among different supports, YSZ shows greater selectivity to partial oxidation than the complete combustion, as the selectivity to CO is much greater than that to CO2.…”
Section: 2supporting
confidence: 90%
“…Peaks at the lower region are almost the same but there is a shoulder peak for un-modified sample in the moderate temperature region in the TPR profile. It has been reported that the reduction becomes easier while the energy of the metal–oxygen bond decreases [ 32 ]. The peaks at moderate temperature regions can be attributed to the reduction of Ni 3+ to Ni 2+ .…”
Section: Resultsmentioning
confidence: 99%